Powder, § 2, MASS ACTS (Rockwell & Churchill 1889) (Passed 1645). - (:unkn) unknown (General Publisher, 1645)
That no Perso (except for the defence of themselves and their vessels at Sea) shall transport any Gunpowder out of this jurisdiction, without License first obteined, from some two of the Magistrates, upon penalty of forfeiting all such powder as shall be transporting or transported, or the value thereof;"
--
Keywords: GUN POWDER TRANSPORTATION